THE INFLUENCE OF PRICE AND INCOME OF MUSLIM CONSUMERS ON PURCHASING DECISIONS OF BERKAH BARUS SYRUP PRODUCTS FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Simamora, Satria Iam Syafii; Imsar, Imsar; Dharma, Budi (Pena Cendekia Insani, 2026)
This study aims to analyze the influence of price and income of Muslim consumers on purchasing decisions for Berkah Barus Syrup products from an Islamic economic perspective. The study used a quantitative approach with an associative design. Data were collected through a Likert scale questionnaire (1–5) distributed to 80 Muslim consumer respondents in Barus District, Central Tapanuli Regency, who were selected using a random sampling technique. Data analysis was performed using multiple linear regression using SPSS version 29, supported by validity and reliability tests, and classical assumption tests. The results showed that price had a positive and significant effect on purchasing decisions, as did consumer income, which had a positive and significant partial effect. Simultaneously, price and income were proven to have a significant effect on purchasing decisions for Berkah Barus Syrup products. These findings indicate that price suitability with Muslim consumers' income levels is an important factor in forming purchasing decisions. This study provides an empirical contribution to the development of Muslim consumer behavior studies by integrating the concept of purchasing decisions with Islamic economic principles, particularly in the context of price fairness and consumer welfare. The practical implications of this study can serve as a reference for business actors in formulating pricing strategies that are in accordance with sharia values and consumers' economic conditions.